The Nineties - Klosterman, Chuck, 1972- (New York : Penguin Press, 2022)
"Essays about 1990s popular culture, politics, sports, literature, music"--.
new book 2022 spring.
Includes bibliographical references (pages 341-354) and index.
Keywords: Popular culture -- United States -- History -- 20th century; Civilization; Social Life and Customs; Intellectual life; United States -- Civilization -- 1970-; United States -- Social life and customs -- 1971-; United States -- Intellectual life -- 20th century